Implementation of Traveling Salesman Problem (TSP) based on Dijkstra's Algorithm in the Information System of Delivery Service - Syahputra, M. Firman Aji; Devita, Riri Nada; Siregar, Sherly Allsa; Kirana, Kartika Candra (JAVA Journal of Electrical and Electronics Engineering, 2016)
Traveling Salesman Problem (TSP) was defined as a task for finding of the shortest route. The finding of the shortest route influences a price of delivery service and profit of company. Therefore, we proposed an implementation of Traveling Salesman Problem (TSP) based on Dijkstra’s Algorithm in a information systems of delivery services